Efeitos do treinamento de estabilização funcional em mulheres saudáveis e com dor femoropatelar - Baldon, Rodrigo de Marche (2014)
Hip and trunk strengthening exercises have been included in preventive programs and treatment protocols for patellofemoral pain (PFP). It is believed that the strengthening of these muscles might change the lower limb movement pattern during functional activities, reducing the patellofemoral stress. However, there is limited evidence about the clinical and biomechanical effects of the treatment focused on hip and trunk muscle strengthening and lower limb and trunk movement control, named functional stabilization training (FST). Thus, the objectives of this thesis were to verify the effects of the FST in healthy females, to compare the effects of the FST to the standard treatment (ST) in females with PFP, and to determine the muscle function mechanism(s) by which the FST leads to kinematic changes in the frontal plane. The 3D kinematics was assessed during the single-leg squat using a camera system and an electromagnetic tracking system. The hip and knee isokinetic torque was assessed with an isokinetic dynamometer and trunk muscle resistance was evaluated by way of sustained static postures. The functional performance was evaluated using the single-leg triple hop test, the timed 6-m single-leg hop test, and the Lower Extremity Functional Scale. The pain intensity was assessed with a 10cm visual analogue scale and the Global Rating of Change Scale was used to measure perceived improvement. The results of this thesis demonstrated that the healthy females and the patients with PFP performing the FST decreased the movement excursion of contralateral pelvis depression, hip adduction and knee abduction. Moreover, the patients performing the FST also decreased ipsilateral trunk inclination and increased pelvis anteversion and flexion. The FST was also effective in increasing hip and knee torque and functional performance in healthy females and in the patients with PFP as well as the trunk muscle endurance in PFP patients. The patients who performed the FST also showed less knee pain intensity and greater perceived improvement when compared to the patients who performed the ST. Finally, the strengthening of the gluteus muscles was associated with improvement of lower limb and trunk kinematics in the frontal plane. Therefore, the results of this thesis show that the FST causes significant lower limb biomechanical effects in healthy females and in patients with PFP. Moreover, the FST causes greater clinical improvements in patients with PFP when compared to the ST.